Antibodies to cannabinoid type 1 receptor co‐react with stomatin‐like protein 2 in mouse brain mitochondria. Issue 3 (26th April 2013) - Morozov, Yury M.; Dominguez, Martin H.; Varela, Luis; Shanabrough, Marya; Koch, Marco; Horvath, Tamas L.; Rakic, Pasko
Abstract Anti‐cannabinoid type 1 receptor (CB1) polyclonal antibodies are widely used to detect the presence of CB1 in a variety of brain cells and their organelles, including neuronal mitochondria. Surprisingly, we found that anti‐CB1 sera, in parallel with CB1, also recognize the mitochondrial protein stomatin‐like protein 2. In addition, we show that the previously reported effect of synthetic cannabinoid WIN 55, 212‐2 on mitochondrial complex III respiration is not detectable in purified mitochondrial preparations. Thus, our study indicates that a direct relationship between endocannabinoid signaling and mitochondrial functions in the cerebral cortex seems unlikely, and that caution should be taken interpreting findings obtained using anti‐CB1 antibodies.